How Does Carbon Footprint Information Affect Consumer Choice? A Field Experiment - Bianca Beyer; Rico Chaskel; Simone Euler; Joachim Gassen; Ann-Kristin Großkopf; Thorsten Sellhorn (Journal of Accounting Research, 2023)
This paper reports the results of a field experiment investigating how attributes of carbon footprint information affect consumer choice in a large dining facility. Our hypotheses and research methods were preregistered via the Journal of Accounting Research's registration-based editorial process. Manipulating the measurement units and visualizations of carbon footprint information on food labels, we quantify effects on consumers' food choices. Treated consumers choose less carbon-intensive dishes, reducing their food-related carbon footprint by up to 9.2%, depending on the treatment. Effects are strongest for carbon footprint information expressed in monetary units (“environmental costs”) and color-coded in the familiar traffic-light scheme. A postexperimental survey shows that these effects obtain although few respondents self-report concern for the environmental footprint of their meal choices. Our study contributes to the accounting literature by using an information-processing framework to shed light on the information usage and decision-making processes of an increasingly important user group of accounting information: consumers.
Keywords: 650; information processing; carbon footprint; consumers; decision making; field experiment